The temporal dipole moments of solute molecules undergoing charge transfer - Krzysztofowicz, Andrzej; Tomin, Vladimir I. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The expression for time dependence of excited state dipole moment of molecule with charge transfer on the correlation function of instant spectra kinetics has been deduced on the basis of the theory of solvatochromism. Time dependence of excited state dipole moment of well known luminescence probe 6-propionyl-2-dimethylaminonaphtalene in polar solvent is presented.
Optica Applicata, Vol. 36, 2006, nr 4, s. 483-487
Keywords: optyka; time dependences; dipole moment; charge transfer